Washback effects of c1-level test on students’ english learning motivation as perceived by 2nd- year mainstream students, FELTE, ULIS, VNU = Ảnh hưởng của kì thi c1 lên động lực học tiếng Anh của học sinh theo nhận thức của sinh viên năm 2 mainstream, KHOA SPTA, ĐHNN, ĐHQGHN - Đình, Thị Thùy (2020)
The globalization makes English learning become very important to the modernization and industrialization of Vietnam. To meet “Basic requirements of English teachers” set by MOET, 2nd-year mainstream students at ULIS have to take C1-level test at the end of the second year at the university. This test affects their learning significantly. Since there is little research on this in Vietnam, this study was carried out to investigate the washback effects of C1-level test on students’ English learning motivation in the perception of 2nd-year mainstream students at FELTE, ULIS. Hopefully, the research would be a source of reference for the teachers and leadership to understand how students’ motivation changed during preparing for the test. Descriptive statistics was employed to explore the washback effects of the test on students’ English learning motivation. 200 2nd-year mainstream students at FELTE were chosen by cluster sampling method. A questionnaire of 30 close-ended questions and one open-ended one together with semi-structured interview were utilized to collect data, studying changes in students’ English learning motivation, factors affecting it and students’ solutions to negative effects of the test on their learning motivation during preparing for C1-level test. The findings indicated that motivation of more than half of the students increased, that their English learning motivation for practical purposes positively changed most, and that major causes of students’ decrease in motivation were ineffectiveness of the syllabi, worsened self-image, lacks of self-regulatory strategies and grades. In addition, students mainly enhanced their learning interest, improved English competence and built learning strategies to motivate themselves. These findings suggest that the syllabi need to be more flexible and useful for the students to prepare for the test. Moreover, teachers should create chances for the students to share learning approaches and test-oriented learning strategies and pay more attention to students’ different learning styles and strategies in delivering the lessons.